Manpower Recruitment Agencies in Nepal - Dahal, Kapil Babu (NUTA Journal, 2023)
The daily exodus of an increasing number of Nepali to many foreign nations has a significant economic influence on the country. It is not a new phenomenon in Nepal for people to migrate outside to seek work. Still, it is a relatively new practice in Nepal to facilitate overseas migration through employment agencies. Nepal's liberal democratic atmosphere, openness, and the nationwide spread of the Maoist insurgency contributed to a dramatic rise in transnational movements in the country midway through the 2000s. Over this period, there was a notable increase in the number of Nepalis using brokering agencies and their agents to help them migrate out of Nepal, mostly to non-traditional locations in India. Moving further from mere focusing on impact of international migration on migrants and their family members, this article discusses the distinguishing features and nature of recruitment agencies that facilitate the worldwide migration of foreign workers from Nepal. This article is based on research that looked at companies that help workers migrate outside of Nepal through migrant recruiting. Since these groups are a part of global networks that assist individuals travelling across borders, their actions have made it simpler to turn Nepalis into commodities on the global market stage. To gain an understanding of the nuances of the topic and to derive meaning from the raw data, the study relied mainly on primary and ethnographic data that were subsequently processed thematically.